Investigation of the relation between the sound velocity in liquids and the mean velocity of the thermal motion of their molecules - Franciszek KUCZERA (Archives of Acoustics)
It is shown in this paper that in assuming a rectangular potential well we also assume that the intermolecular compressibility of a liquid. consists of a kinetic and a potential part. It was accepted that the kinetic part – as for a perfect gas – is independent of temperature at constant pressure. Hence, it can be concluded that the temperature coefficients of both the compressibility and the sound velocity depend almost exclusively on the space filling.